2007
DOI: 10.1128/aem.02849-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lipid Composition and Lipid Peroxidation in the Sensitivity of Fungal Plant Pathogens to Aluminum Chloride and Sodium Metabisulfite

Abstract: Aluminum chloride and sodium metabisulfite have shown high efficacy at low doses in controlling postharvest pathogens on potato tubers. Direct effects of these two salts included the loss of cell membrane integrity in exposed pathogens. In this work, four fungal potato pathogens were studied in order to elucidate the role of membrane lipids and lipid peroxidation in the relative sensitivity of microorganisms exposed to these salts. Inhibition of mycelial growth in these fungi varied considerably and revealed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
0
22
0
5
Order By: Relevance
“…There have been numerous studies suggesting that these salts may represent an interesting alternative to synthetic fungicides. Recent literature also suggests that aluminium chloride is among the most efficient salts to control postharvest pathogens (Hervieux et al ., ; Mecteau et al ., , ; Mills et al ., , , ; Yaganza et al ., ; Avis et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…There have been numerous studies suggesting that these salts may represent an interesting alternative to synthetic fungicides. Recent literature also suggests that aluminium chloride is among the most efficient salts to control postharvest pathogens (Hervieux et al ., ; Mecteau et al ., , ; Mills et al ., , , ; Yaganza et al ., ; Avis et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…No effective alternative to sulphur dioxide (SO 2 ) has been found for the table grape industry, despite much research and development. SO 2 and sulphites are effective against a broad spectrum of pathogens; they are thought to act directly on the pathogen through their strong nucleophilic properties, inactivating key regulatory proteins and altering membrane integrity (Avis, Michaud & Tweddell 2007). However, plants have developed numerous inducible mechanisms to cope with abiotic and biotic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the similarities of our results with those mentioned above regarding relative sensitivity to Phi between oomycetes and fungi, to make extrapolations of the sensitivity of these pathogens to the entire kingdoms could be a mistake, because significant differences in the sensitivity to phosphorous acid related compounds were found within various classes of Oomycetes, and moreover, within a species (BASHAN et al 1990;WILKINSON et al 2001). On the other hand, AVIS et al (2007) reported that sensitivity to low doses of aluminum chloride and sodium metabisulfite, two chemicals capable of controlling post-harvest pathogens on potato tubers, showed similar behaviour in terms of relative sensitivity between oomycetes and fungi as in the present study with phosphites. In that report, they showed that EC 50 s of aluminum chloride and sodium metabisulfite for P. infestans, R. solani and F. sambucinum also differed in at least one order of magnitude, being the oomycete the most sensitive of these pathogens analysed.…”
Section: Discussionmentioning
confidence: 35%